(untitled) - Cameron, Scott (Singapore, 2008)
Hemispheres is a four-level integrated skill series for adults and young adults that puts skills-building back into integrated skills! The course is uniquely suitable for students either studying general English language or those studying English with a view toward more academic work. The series strategically develops both language skills and critical thinking skills. The thought-provoking topics and appealing user-friendly design invite learners into the skills development without hesitation.
Keywords: English language,Ngôn ngữ tiếng Anh